Indian microfinance : the challenges of rapid growth - Ghate, Prabhu (Thousand Oaks, Calif. : Sage Publications, 2007)
This book provides an overview of the main challenges facing the sector, the progress of its main delivery models, issues relating to the emerging microfinance services of microinsurance and money transfers, ongoing efforts in training and capacity building, opportunities facing commercial financiers such as bankers and the social venture capitalists, and an account of ongoing research in the sector.
Includes bibliographical references and index.
osa 07/05/13
Loans
Keywords: Microfinance -- India; Poor -- India